2023
DOI: 10.1002/chem.202203347
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Thiyl Radical‐Mediated Desilylation of Arylsilanes

Abstract: A straightforward, visible‐light triggered desilylation of arylsilanes by thiyl radicals is presented. Silyl groups are often used to block a reactive position in multi‐step organic synthesis, for which a mild cleavage at a late‐stage will provide new possibilities and disconnection routes by CAr−Si cleavage/deprotection. In this work, commercially available and cheap disulfides are employed for the first time in this type of C(sp2)‐Si bond cleavage reactions. Thus, upon irradiation with visible‐light, homolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…1A** can result in the formation of Int. 7A via S N 1 pathway after the loss of hexamethyldisiloxane (observed in 29 Si NMR: δ=9.67 ppm, CDCl 3 ) [25] . DFT calculation revealed that the S N 1 is the favoured pathway (low energy of Int.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A** can result in the formation of Int. 7A via S N 1 pathway after the loss of hexamethyldisiloxane (observed in 29 Si NMR: δ=9.67 ppm, CDCl 3 ) [25] . DFT calculation revealed that the S N 1 is the favoured pathway (low energy of Int.…”
Section: Resultsmentioning
confidence: 99%
“…7A via S N 1 pathway after the loss of hexamethyldisiloxane (observed in 29 Si NMR: δ = 9.67 ppm, CDCl 3 ). [25] DFT calculation revealed that the S N 1 is the favoured pathway (low energy of Int. 6A) instead of the S N 2 pathway (because of the high energy of TS 1A), as shown in Figure 3.…”
Section: (A) With Electron-poor Anilinementioning
confidence: 99%
“…This resulted in the formation of aryl radicals 31.4 and desilylated derivatives 31.3 from it through a HAT step (Scheme 31). 159…”
Section: Intermediate Free Reactionsmentioning
confidence: 99%